3D motion graphics for 2D artists : conquering the 3rd dimension - Byrne, Bill, 1976- (Focal Press, 2012)
Add 3D to your mograph skillset! For the experienced 2D artist, this lavishly illustrated, 4 color book presents the essentials to building and compositing 3D elements into your 2D world of film and broadcast. Concepts and techniques are presented in concise, step-by-step tutorials, hundreds of which are featured throughout. Featured applications include Photoshop, Illustrator, After Effects, and Cinema 4D. Lessons include exploring the expanded 3D functionality of the Adobe Creative Suite applications (After Effects, Photoshop, and Illustrator) through a series of practical tutorials. More advanced lessons then follow, with tutorials and insight provided in specifically geared lessons for 2D artists working in Cinema 4D, 3ds Max, and ZBrush. 4-color presentation is further enhanced by various sidebars, tips, and "gotchas" to watch for through-out the book. The DVD contains hours of project files with which you can work along the tutorials in the book. * Full of step-by-step tutorials that will greatly enhance your novice 3D skills in a matter of minutes * 4-color illustrations and artist profiles provide you with artistic and practical inspiration * The companion DVD includes project files for you to work with yourself, as well as video instruction, providing visual instruction for techniques presented in the book